Stress alleviation of Filipino school counselors using cognitive behavioral therapy - Aguinaldo, Cleopatra Daisy T.
The purpose of the study was to gather, compare, and analyze facts concerning the application of Cognitive Behavioral Therapy in reducing stress of counselors in Quezon City. Using the mixed method explanatory design, qualitative approach through thematic analysis and the quantitative approach through one group pretest-postest design were employed. Ten high school counselors participated in the study. The Cohen Perceived Stress Scale was used to determine the participants’ level of perceived stress before and after exposure to an intervention, while Cognitive Behavioral Therapy was conducted as a program for reducing their stress levels. Results showed that counselors’ stressors include aspects of personal, intrapersonal, organizational, environment and private life. Their coping strategies and techniques include confrontative coping, positive reappraisal, social support, planful problem solving, self control, and acceptance of responsibility. Likewise, it was found out that prior to the exposure to the program, counselors were on the average perceived stress level. Changes were evident in the posttest scores of the counselors after exposure to intervention. Filipino School Counselor’s perceived stress diminished remarkably. The results of the study may be used by counselor-educators in developing responsive programs, through psycho-education and counseling, using Cognitive Behavioral Therapy in helping fellow counselors manage difficult situations.